1997
DOI: 10.1121/1.418332
|View full text |Cite
|
Sign up to set email alerts
|

Articulatory strengthening at edges of prosodic domains

Abstract: In this paper it is shown that at the edges of prosodic domains, initial consonant and final vowels have more extreme (less reduced) lingual articulations, which are called articulatory strengthening. Linguopalatal contact for consonants and vowels in different prosodic positions was compared, using reiterant-speech versions of sentences with a variety of phrasings read by three speakers of American English. Four prosodic domains were considered: the phonological word, the phonological (or intermediate) phrase… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

31
487
5
21

Year Published

1999
1999
2017
2017

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 730 publications
(544 citation statements)
references
References 11 publications
31
487
5
21
Order By: Relevance
“…a corp), while in the preposition condition she uttered a two-syllable word (acorp). The phonetic realization of a sequence is affected by the location of (prosodic) word boundaries (Fougeron & Keating, 1997;Turk & Shattuck-Hufnagel, 2000); the word boundaries intended by the speaker could have been marked by acoustic cues useful to the children (Gout, Christophe, & Morgan, 2004).…”
Section: Additional Resultsmentioning
confidence: 99%
“…a corp), while in the preposition condition she uttered a two-syllable word (acorp). The phonetic realization of a sequence is affected by the location of (prosodic) word boundaries (Fougeron & Keating, 1997;Turk & Shattuck-Hufnagel, 2000); the word boundaries intended by the speaker could have been marked by acoustic cues useful to the children (Gout, Christophe, & Morgan, 2004).…”
Section: Additional Resultsmentioning
confidence: 99%
“…Segmental lengthening is likely to coincide with or trigger the realization of other acoustic cues, such as a larger pitch movement or degree of articulation. For example, in an analysis of linguopalatal contact in reiterant speech, Fougeron and Keating (1997) have shown that vowels are produced with greater articulatory magnitude in final position in the prosodic domain. Some or all of these acoustic cues may contribute to the postulation of a prosodic boundary, in proportion to the degree to which each cue is predictive of a word boundary.…”
Section: Discussionmentioning
confidence: 99%
“…The prosodic structure of an utterance can also affect segmental articulation. Fougeron and Keating (1997), for example, showed that segments located in the immediate vicinity of the edge of a prosodic domain (in particular, initial consonants and final vowels) have more extreme lingual articulation, a phenomenon they refer to as articulatory strengthening. Because the boundaries of prosodic words, accentual phrases, and any higher prosodic domains are always aligned with a lexical-word boundary, any acoustic cues marking the edge of these prosodic domains could help disambiguate monosyllabic, embedded words from their carrier words before post-offset information is heard.…”
Section: Introductionmentioning
confidence: 99%
“…The internally layered foot in Dutch protected from undergoing weakening processes and/or they can become the target of strengthening effects (e.g., Trubetzkoy 1969Trubetzkoy [1939; Steriade 1994;Byrd 1996;Beckman 1998;Casali 1998;Alber 2001;Smith 2005;Cabré and Prieto 2006;Becker et al 2012;Fougeron and Keating 1997;Keating et al 2003;Selkirk 2011). To capture the dual patterning of unstressed vowels in Dutch and, more specifically, the fact that in the semi-formal register not all unstressed vowels reduce (e.g., [ˌlokəmo'tif], rather than [ˌlokəmə'tif]), we propose that the positional constraint in (32) …”
Section: (32) Initialfoot-ident[feature] (Abbr Initialft-ident[f])mentioning
confidence: 99%